THE QUALITY OF BOAR FROZEN SEMEN DILUTED IN BTS AND MII WITH DIFFERENT CRYOPROTECTANT SUPPLEMENTED WITH SODIUM DODECYL SULPHATE - Frederika Katerina Foeh, Nancy Diana; Arifiantini, Raden Iis; Yusuf, Tuty Laswardi (Jurnal Kedokteran Hewan, 2017)
This research was aimed to study the effect of administration of glycerol and dimetilacetamida (DMA) in BTS and MIIIextender supplemented with sodium dodecyl sulphate (SDS) on boar frozen semen. A number of four boars were used in this study for semen collection (n=20). The collected semen was evaluated both macroscopically and microscopically. In this study, only the semen that demonstrated70% sperm motility, 200.106/mL sperm concentration, and20% sperm abnormalities were used and divided into eight tubes. A number of 4 tubes were diluted with 5 mL of BTS, and the rest with 5 mL MIII. The sampel was stored at 20-22 C for 2 hours, followed by centrifugation for 15 minutes (at 2000 rpm), and taken of pellet with 1 ml supernatant. The pellet that was resulted from centrifugation using BTS, then re-diluted with BTS-glycerol 5% (BTSG), BTS DMA 5% (BTSD), BTS-glycerol 5% and SDS (BTSG-S), BTS-DMA 5% and SDS (BTSD-S). Four other pellets that were centrifuged with MIII also re-diluted with MIII-glycerol 5% (MIIIG), MIII-DMA 5% (MIIID), MIII-glycerol 5% and SDS (MIIIG-S), MIII-DMA 5% and SDS (MIIID-S). Next, all of diluted semen were inserted into 0.5 mL straw and equilibrated for 2 hours (4 C), then frozen and stored in liquid nitrogen. The evaluation of frozen semen quality was conducted at 24 hours after frozen. The result of this study showed that post-thawing motility of spermatozoa in BTSD-S (40.170.2%) was found higher (P0.05) compared to seven other dilution processes. Therefore, it is concluded that the concentration of 5% DMA that supplemented with SDS in BTS dilution much better for maintaining boars frozen semen quality.